PENGARUH BIAYA PROMOSI TERHADAP VOLUME PENJUALAN MOTOR BEKAS DI SHORUM BUDI MOTOR KOTA BENGKULU - Rina risna Yanti; Sulisti Afriani (Universitas Prof.Hazairin,SH Bengkulu, 2019)
Study aims to determine how much influence promotion costs have on the sales volume of second motorcycle at showroom budi motor bengkulu city. Based on the results of the study, the regression equation of the influence of variable X on the Y variable is Y = 43,041 + 1,0226X, which means that the increase in sales volume goes hand in hand with promotion, this can be seen from the calculation of the regression coefficient value (b) positive. In the sense that each increase of 1 rupiah issued by the company for promotional costs will increase the sales volume by 1,0226 units sales of second motorcycle Simple correlation value r value (correlation coefficient) Positive and strong influence, this can also be seen the r value of 0.27 and the value of kd = 27%, meaning that any increased promotion costs will have an impact on increasing sales volume of second motorcycle products showroom budi motor bengkulu city. The t-test shows that promotion costs have a positive and significant effect on the sales volume of second motorcycle on showroom budi motor bengkulu city, so that obtained tcount obtained is 1.4864 smaller than t table at an error rate of 5% then t-table is 2.0739. This is in line with the Test-t criteria, namely that if tcount is smaller than t-table, then Ho is accepted and H1 is rejected, meaning that there is a significant effect between the cost of promotion on the volume of second motorcycle sales in showroom budi motor bengkulu city